Digital Teaching Materials Text Observation Result Reports (LHO) Based on Local Wisdom for Middle School Students - Sobrina; Gloriani, Yusida; Khaerudin, I. Robia (International Journal of Educational Research Excellence (IJERE), 2025)
This research aims to develop digital teaching materials for observation report text (LHO) based on the local wisdom of junior high school students. The problems of this research are as follows: (1) How can we develop digital teaching materials for text reports based on local wisdom for junior high school students? (2) What are the results of the implementation of digital teaching materials and text reports based on observations and local wisdom for junior high school students? This study uses research and development methods with the (Analysis Design Development Implementation Evaluate) model. The steps of this research consisted of needs analysis, designing digital teaching materials for observation report texts, developing digital teaching materials for observation report texts, product implementation of digital teaching materials for observation report texts, and evaluation of digital teaching materials for observation report texts. Data collection in this study was conducted by collecting data from the results of validation questionnaires from learning model experts, media experts, practitioners, and implementation in learning. The data obtained were analyzed descriptively using a Likert scale and Paired Sample T-Test. The results of the validation test by material experts obtained a value of 3.9; validation test by media experts obtained a score of 3.2; validation test by an Indonesian language teacher obtained a score of 3.85; The results of the implementation of digital teaching materials, observation report text based on local wisdom for junior high school students, received a positive response from students with a score of 3.7. The conclusions of this research show that digital teaching materials report texts based on observations based on local wisdom for junior high school students, meet the criteria, and are suitable for use as a learning model by teachers in Indonesian language subjects and observation report text material in class VIII junior high school students